2008
DOI: 10.1159/000167022
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin K<sub>2</sub> Inhibits the Growth of Hepatocellular Carcinoma via Decrease of Des-Gamma-Carboxy Prothrombin

Abstract: Background: Des-γ-carboxy prothrombin (DCP) is a serum protein produced by hepatocellular carcinoma (HCC) cells in the absence of vitamin K. Serum and tissue DCP expressions are thought to reflect the biological malignant potential of HCC. Hence, we aimed to examine the efficacy of vitamin K2 on the production of DCP as well as tumor cell growth and invasion. Methods: Cell growth and viability were evaluated by 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide assay. The in vivo efficacy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…Recent studies by the current authors and other researchers found that des-γ-carboxy prothrombin (DCP), an abnormal cytokine secreted by HCC cells, was involved in the activation and regulation of downstream pathways of the c-Met signaling system in vitro and in animal studies (17)(18)(19)(20). Thus, whether or not DCP and c-Met are co-expressed in human HCC and whether their co-expression is correlated with tumor recurrence are questions of great interest.…”
Section: Introductionmentioning
confidence: 94%
“…Recent studies by the current authors and other researchers found that des-γ-carboxy prothrombin (DCP), an abnormal cytokine secreted by HCC cells, was involved in the activation and regulation of downstream pathways of the c-Met signaling system in vitro and in animal studies (17)(18)(19)(20). Thus, whether or not DCP and c-Met are co-expressed in human HCC and whether their co-expression is correlated with tumor recurrence are questions of great interest.…”
Section: Introductionmentioning
confidence: 94%
“…The level of DCP in supernatant of cell culture was determined by an electrochemiluminescence immunoassay. The results showed that Vitamin K 2 (2-40 μM) significantly decreased DCP production [43]. Importantly, the effect of vitamin K 2 on DCP production was observed in nude mice bearing HCC xenografts.…”
Section: The Causes and Mechanisms Of Dcp Productionmentioning
confidence: 99%
“…Importantly, the effect of vitamin K 2 on DCP production was observed in nude mice bearing HCC xenografts. As a result of vitamin K 2 administration, the capacity of HCC xenografts was obviously inhibited [43]. In clinical studies, Ishizuka et al evaluated the effects of menatetrenone, which is a vitamin K 2 analog, on recurrence of hepatocellular carcinoma after surgical resection.…”
Section: The Causes and Mechanisms Of Dcp Productionmentioning
confidence: 99%
“…The K vitamins have been shown to possess weak anti-HCC growth activity in vitro and in animal models. [8][9][10] Recently it has also been reported that vitamin K2 can decrease HCC recurrences post-surgical resection 32 and may even inhibit human hepatocarcinogenesis. 33 Sorafenib, a recently FDA-approved multi-kinase inhibitor for phosphorylation by vitamin K1 plus sorafenib combination and PKA inhibitor H89 had no effect on vitamin K1 plus sorafenib inhibition of Raf kinase activity.…”
Section: Discussionmentioning
confidence: 99%